Alpha-synuclein seeding amplification assays in Lewy body dementia: a brief review - Maria Bregendahl; Zeynep Bengisu Kaya; Wolfgang Singer; Pamela J. McLean (Molecular Neurodegeneration)
Abstract Lewy body dementia (LBD), which includes dementia with Lewy bodies (DLB) and Parkinson’s disease dementia (PDD), is characterized by cognitive decline, sleep disturbances, motor dysfunction, and other debilitating clinical symptoms. Neuropathologically, LBD is characterized by the progressive accumulation of alpha-synuclein (aSYN) in vulnerable cellular populations in the brain. Diagnosing LBD is challenging due to the overlap of clinical symptoms with Alzheimer’s disease (AD) and other neurodegenerative disorders with current diagnostic tools, including clinical examinations by specialized neurologists and brain imaging, limited by accessibility. Taken together, LBD is often misdiagnosed, especially at early disease stages. Seed amplification assays to detect pathogenic aSYN (aSYN SAAs) are emerging as promising tools to detect aSYN pathology in biological specimens. These assays amplify trace amounts of misfolded aSYN, enabling their potential detection in brain, CSF, saliva, skin, and blood. This review compares the sensitivity and specificity of aSYN SAAs across different biological samples and explores the potential of the assay as a diagnostic in LBD. We also highlight challenges that will need to be addressed going forward if the aSYN SAA is to be widely adopted as a diagnostic test. Despite current limitations, aSYN SAAs hold promise for early and precise diagnosis, paving the way for targeted treatments that could significantly improve patient care and outcomes.